2012
DOI: 10.1177/0256090920120205
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Commitment and Job Satisfaction among Teachers during Times of Burnout

Abstract: Organizations want to maximize productivity by minimizing stress, as increased levels of stress and burnout may have significant implications for organizational performance such as reduced job satisfaction and lowered organizational commitment. Also certain occupations are linked more to burnout than the others. The present exploratory study undertakes the examination of burnout among teachers in the university as they are an essential part of a successful educational system. Organizational commitment is essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
1
22

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 100 publications
7
90
1
22
Order By: Relevance
“…Hsu and Chen (2012) observed that those university faculty members who achieved a higher organizational commitment score while they held a higher degree of the job satisfaction. Nagar (2012) reported that the higher job satisfaction made greater contribution for organizational commitment. Suma and Lesha (2013) examined that satisfaction with work-itself, the quality of supervision and pay satisfaction had significant positive impact on organizational commitment among municipality employees working in Shkoder.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Hsu and Chen (2012) observed that those university faculty members who achieved a higher organizational commitment score while they held a higher degree of the job satisfaction. Nagar (2012) reported that the higher job satisfaction made greater contribution for organizational commitment. Suma and Lesha (2013) examined that satisfaction with work-itself, the quality of supervision and pay satisfaction had significant positive impact on organizational commitment among municipality employees working in Shkoder.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…It is no longer a hidden fact that many civil servants in Nigeria are not well paid anymore especially in Osun State and this development tends to make these workers feel bored and lose interest in their work. Nagar (2012) opines that an employee who experiences high level of stress may not be able to perform effectively in his/her job. Poor service delivery might even lead to incompetence and high level of inferiority complex.…”
Section: Introduction Background To the Studymentioning
confidence: 99%
“…Therefore, in this study, WC is conceptualized as employees' level of identification and involvement with and loyalty to the employing organization (Lok et al, 2005). Studies have investigated WC as a predictor of occupational burnout (Nagar, 2012;Roy & Avdija, 2012). While some findings showed that WC significantly correlates with occupational burnout (Nagar, 2012) others showed no significant relationship (Dick & Wangener, 2002).…”
mentioning
confidence: 99%
“…Studies have investigated WC as a predictor of occupational burnout (Nagar, 2012;Roy & Avdija, 2012). While some findings showed that WC significantly correlates with occupational burnout (Nagar, 2012) others showed no significant relationship (Dick & Wangener, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation